DINAMIKA PENGGUNAAN MEDIA PEMBELAJARAN DAN ANTUSIAS BELAJAR SISWA DALAM INTERAKSI KELAS - Rachmat Panca Putera; Dwi Nadya Cahyanti; Sri Handayani; Lesya Ningsih; Alisa Adelia (CV JK Riset Publishing Group, 2025)
This study aims to examine the dynamics of instructional media use and students’ learning enthusiasm within classroom interactions at Madrasah Ibtidaiyah (MI) Negeri 1 Lampung Timur. Employing a qualitative approach with a descriptive-interpretative design, the study involved third- and fourth-grade students as well as classroom teachers directly engaged in the learning process. Data were collected through classroom observations, semi-structured interviews, and document analysis, and were analyzed thematically to identify patterns of interaction and the meanings constructed by students during learning activities. The findings indicate that instructional media function as pedagogical mediators that shape students’ learning enthusiasm through classroom interaction. In Grade III, instructional media primarily serve as affective stimuli that generate interest and positive emotions, resulting in situational enthusiasm. In contrast, in Grade IV, instructional media act as dialogical tools that foster more reflective and sustained learning engagement. These findings demonstrate that students’ learning enthusiasm does not arise automatically from the presence of instructional media, but is constructed through teachers’ pedagogical strategies in mediating media use. This study highlights the importance of dialogical, contextual, and developmentally appropriate use of instructional media to support meaningful classroom interaction.